Auditors and Independence - World Bank (World Bank, Washington, DC, 2012)
Independence is a concept of fundamental importance in business relations and corporate governance. It is above all crucial in auditing, which provides a guarantee of the integrity of the numbers on which an efficient allocation of capital within the capital market system depends. The job of auditors is to express an independent opinion on whether financial statements are reliable and credible. They report on the statements' compliance with the law and accounting standards and, depending on the jurisdiction, whether the accounts prepared by the board reveal either a fair, or a true and fair, picture of economic reality.